A Review on Literature in Governance of Islamic Banking (2005-2015) - Muhammad Ridhwan Ab. Aziz; Nik Mohd Fadhil Nik Mohammad; Musa Manjang; Mohd Farhan Mohd Salleh; Raihan Nasir (Australasian Center for Research and Development (ACRD), 2024)
One of the key elements for the success and performance of Islamic banking institutions is the structuring of good and sound cooperate governance. Forming and planning good corporate governance for Islamic banking institutions is an important attempt to make sure the institutions are well protected. There are various management and planning elements in corporate governance geared toward good corporate governance purely for Islamic banking institutions. Thus, the objective of this article is to examine the related literatures on governance for Islamic banking institutions between 2005 and 2015. The methodology of this article is through qualitative research based on document analysis on the previous articles and literatures on governance of Islamic banking. Data from each article related in this field were collected and statistically analyzed using the Statistical Product and Service Solution software. This study looked at variables which include authorship patterns, number of articles published, and author productivity. The general finding in this article shows that there are still a limited number of articles and papers published by the researchers related to this field. Henceforth, this article provides significant suggestions and strategies for the future exploration on governing and planning for good corporate governance for the Islamic banking institutions.